Museum Virtual Tour Development Using 3D Vista as a History Learning Source - Syukur, Syarifuddin; Dewie, Siti Swasti Eka; Oktarina, Santi (Universitas Pendidikan Ganesha, 2022)
Visits to museums are also a means of learning that arouses curiosity and provides a different nuance in learning. The problem today is that distance and time are not possible if the teacher brings students to the location of the museum. An alternative solution to these problems is to use technology. This study aims to develop a virtual tour learning tool at the Sriwijaya museum by using the 3D Vista application as a source for learning history. The stages of this research adapt to the product development research model of Alessi and Trollip, namely design, planning, and development. The device developed was validated by experts and tested on the subjects 30 student of class X at senior high school. The trial design in this study used a one group pretest and posttest design. Data collection techniques include interviews, tests, and questionnaires. The data analysis technique used analysis of the results of interviews, tests, and questionnaires. The result of this study are, 1) the developed learning tools have been tested for validity after going through validation with 4 experts; 2) virtual tour museum learning resources have been tested for practicality with a practicality percentage of 87.87%; and 3) the effectiveness of the device consisting of student activities in the learning process obtained an N-Gain of 5.57 with a medium category. The conclusion of this study is that the learning tools developed were tested to be valid, practical, and effective.